Analisis Total Asset Turnover, Net Profit Margin dan Return On Investment Dalam Menilai Kinerja Keuangan Koperasi - Nugraha, Deni; Wahyudin, Wahyudin (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2025)
The results of this study show that the financial performance of the cooperative is in a very unhealthy position as indicated by the TATO calculation result of 0.13 times, while in the healthy category as indicated by the NPM calculation result of 12.32% and then in an unhealthy condition in the ROI calculation result of 1.51 times. These things are caused by a decrease in sales levels, decreasing SHU due to large operational costs and suboptimal use of assets.